Mindfulness to improve executive and cognitive processes in gifted children - Claudia Arévalo-Proaño; Yolanda Dávila; Fernanda Álvarez-Cárdenas; María José Peñaherrera-Vélez; Ximena Vélez-Calvo (INFAD, 2019)
Gifted people are characterized by their particular curiosity and varied interests, a high level of verbal aptitude, fast learning and good reasoning. However, they can also be socially vulnerable due to their limited social skills. In certain cases they also tend to be inflexible and have little emotional self-regulation. Several intervention techniques have been used to improve these cognitive and executive processes (metacognitive and emotional), including Mindfulness or full attention in the “here and now”, which is responsible for increasing awareness of the present, developing self-observation and promoting social and emotional well-being. The aim of this work is to analyze the effect of Mindfulness in the executive and cognitive processes of gifted children, through an exhaustive review of original research articles published in the last five years. We obtained 16 articles: 8 quantitative and 8 literature review. These works conclude that the use of Mindfulness helps to properly manage the executive- cognitive processes and to develop social skills. On the other hand, these processes are enhanced when the family participates in this form of intervention.